Hierarchically structured porous materials : from nanoscience to catalysis, separation, optics, energy, and life science - Su, Bao-Lian; Sanchez, Clément; Yang, Xiao-Yu (Wiley-VCH, 2012)
This first book devoted to this hot field of science covers materials with bimodal, trimodal and multimodal pore size, with an emphasis on the successful design, synthesis and characterization of all kinds of hierarchically porous materials using different synthesis strategies.